Using Asset Disclosure for Identifying Politically Exposed Persons - Rossi, Ivan; Pop, Laura; Clementucci, Francesco; Sawaqed, Lina (World Bank, Washington, DC, 2017)
This paper explores the relationship between two regimes for preventing corruption: the detection and monitoring of politically exposed persons (PEPs) for the purpose of combating money laundering, and asset disclosure requirements for public officials. These regimes are generally designed and implemented separately. Yet as this paper shows, an innovative use of asset disclosure tools could benefit PEP practitioners. The paper seeks to raise awareness of this potential and to connect asset disclosure and PEP practitioners.